Patrimônio cultural e arte: um olhar jurídico e um diálogo contratual - Sampedro, Nancy (2021)
This dissertation aims to study the conflict arising from access to the work of art in the face of the limits imposed by copyright, as well as to analyze how the contract becomes the solution to resolve this conflict of public interest with the private, as it is the intersection that it legitimizes the diffuse right, through the realization of the social function of the cultural object. This work was divided into two titles, departing from the anthropocentric analysis of culture, as this is a dimension of the environment with legal protection, and should be managed through a management system, which will have as main instruments public and the contracts, which will enable the study of the work of art in title two, since art is a genre of culture and, consequently, it also interacts with different areas and subjects, serving as a foundation for the construction of the theory that culture is the basis of contracts that have works of art as their object, due to the positive and negative cultural externalities generated by the legal business, which, in the end, will be analyzed to corroborate the legal interpretation presented in this study. To achieve this purpose, we opted for qualitative and descriptive bibliographic research, based on the deductive methodology